Pengaruh Kurikulum Merdeka Sekolah Penggerak Terhadap Kinerja Guru dan Hasil Belajar Siswa Ilmu Pengetahuan Alam - Yudi Fernandes Hutagalung; Bukman Lian; Djunaidi, Djunaidi (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the influence of implementing the Merdeka Curriculum through the Sekolah Penggerak (Driving School) program on teacher performance and students’ learning outcomes in Natural Science (IPA). The Merdeka Curriculum is designed to provide flexibility for schools and teachers to develop learner-centered instruction, emphasizing the strengthening of competencies and character. The Sekolah Penggerak program serves as a vehicle for implementation, requiring teachers to act as facilitators, innovators, and motivators in the teaching and learning process. This research employed a quantitative approach with an explanatory design. The population consisted of teachers and students in elementary schools that have adopted the Merdeka Curriculum through the Sekolah Penggerak program. Data were collected through questionnaires, classroom observations, and documentation of students’ learning outcomes, and were analyzed using multiple linear regression techniques.These findings highlight that the curriculum’s flexibility, supported by effective management within the Sekolah Penggerak program, fosters innovative and meaningful learning processes.The study recommends strengthening continuous professional development for teachers and ensuring consistent monitoring of implementation so that the Merdeka Curriculum can optimally enhance education quality, particularly in students’ mastery of scientific concepts at the elementary level.